Pharmacogenetic and pharmacokinetic factors for dexmedetomidine-associated hemodynamic instability in pediatric patients - Guan, Yanping; Li, Bilian; Zhang, Yiyu; Luo, Hao; Wang, Xueding; Bai, Xue; Zheng, Zhuoling; Huang, Yaying; Wei, Wei; Huang, Min; Song, Xingrong; Zhong, Guoping (Frontiers in Pharmacology, 2025)
The incidence of hemodynamic instability associated with dexmedetomidine (DEX) sedation has been reported to exceed 50%, with substantial inter-individual variability in response. Genetic factors have been suggested to contribute significantly to such variation. The study was to identify the clinical, pharmacokinetic and genetic factors associated with DEX-induced hemodynamic instability in pediatric anesthesia patients.A cohort of 270 pediatric patients, scheduled for elective interventional surgery, received an intranasal dose of 3 mcg·kg -1 of dexmedetomidine and subsequent propofol induction was conducted when patients had a UMSS of 2-4. The primary endpoint was hemodynamic instability: defined as a composite of hypotension and/or bradycardia, characterized by a 20% reduction from age-specific baseline values. Plasma concentrations of dexmedetomidine were determined, and single nucleotide polymorphisms (SNPs) were genotyped. A validated population pharmacokinetic model was used to estimate pharmacokinetic parameters. Lasso regression was used to identify significant factors and a Cox's proportional hazards model-derived nomogram for hemodynamic instability was developed. Results: Hemodynamic instability was observed in 52 out of 270 patients (209 events), resulting in a cumulative incidence of 16.30% at 90 minutes, as estimated by Kaplan-Meier estimation, and was associated with a median time to event of 35 minutes. The interval time between DEX initiation and propofol induction was 16 min (IQR: 12-22 min). The cumulative incidence was 8.2% within 22 minutes after DEX initiation. The identified significant risk factors included weight, DEX clearance, concomitant propofol use, and the following gene variants UGT2B10 rs1841042 (Hazard ratio (HR):1.41, 95% confidence interval (CI): 1.12-1.79), CYP2A6 rs8192733(HR:0.28, 95%CI:0.09-0.88), ADRA2B rs3813662 (HR:1.39,95%CI:1.02-1.89), CACNA2D2 rs2236957(HR:1.46, 95%CI:1.09-1.96),NR1I2 rs3814057 (HR:0.64, 95%CI:0.43-0.95) and CACNB2 rs10764319 (HR:1.40,95%CI:1.05-1.87) were identified as significant risk factors for DEX-associated hemodynamic instability. The area under the curve for the train and test cohorts were 0.881 and 0.762, respectively. Calibration curve indicated excellent agreement. Conclusion: The predictive nomogram, which incorporates genetic variants (UGT2B10, CYP2A6, ADRA2B, CACNA2D2, NR1I2, and CACNB2), along with clinical factors such as weight, DEX clearance, and propofol use, may help prevent DEX-associated hemodynamic instability. Delayed hemodynamic instability is likely to occur after 35-min DEX initiation in patients with lower DEX clearance after propofol induction.